IMPLIKASI HUBUNGAN KRISTUS DAN BUDAYA DALAM BERBAGAI KONTEKS PENGINJILAN YANG DIHADAPI MURID KRISTUS - Roedy Silitonga (Jurnal Theologia Forum STFT Surya Nusantara, 2020)
This paper is expected to provide direction and encouragement for every disciple of Christ to realize the responsibility of carrying out evangelism and transforming culture on this earth. It is important for Disciples of Christ to understand precisely the relationship between Christ and culture, both in evangelism and in transforming culture. Because by being aware of this, a student can properly carry out evangelism to anyone in diverse cultural contexts. Cultural transformation is only possible by Disciples of Christ who have lived in Christ and are aware of their responsibilities here on earth. Cultural diversity and uniqueness will not weaken a disciple of Christ to preach the gospel properly. Instead the condition is a good opportunity to clear the purpose of the disciples of Christ called and sent by God. Because Christ's disciples not only carry out evangelization of all nations and also transform the culture of anyone who is already in His mandate